Steinernema biddulphi n. sp., a New Entomopathogenic Nematode (Nematoda: Steinernematidae) from South Africa - Cimen, Harun; Půža, Vladimír; NermuŤ, JiŘí; Hatting, Justin; Ramakuwela, Tshima; Hazir, Selcuk (Journal of nematology, 2016)
A new species of entomopathogenic nematode (EPN), Steinernema biddulphi n. sp., was isolated from a maize field in Senekal, Free State Province of South Africa. Morphological and molecular studies indicated the distinctness of S. biddulphi n. sp. from other Steinernema species. Steinernema biddulphi n. sp. is characterized IJs with average body length of 663 μm (606-778 μm), lateral fields with six ridges in mid-body region forming the formula 2,6,2. Excretory pore located anterior to mid-pharynx (D% = 46). Hyaline layer occupies approximately half of tail length. Male spicules slightly to moderately curved, with a sharp tip and golden brown in color. The first generation of males lacking a mucron on the tail tip while the second generation males with a short filamentous mucron. Genital papillae with 11 pairs and one unpaired preanal papilla. The new species is further characterized by sequences of the internal transcribed spacer (ITS) and partial 28S regions (D2-D3) of the ribosomal DNA (rDNA). Phylogenetic data show that S. biddulphi n. sp. belongs to the "bicornutum" clade within the Steinernematidae family.
Keywords: taxonomy; new species; phylogeny; D2-D3; ITS; Steinernema biddulphi; South Africa; entomopathogenic nematodes